2017
DOI: 10.1111/jfpp.13397
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of olive leaf powder on fresh Atlantic horse mackerel (Trachurus trachurus) minced muscle

Abstract: Lipid oxidation is a very complex and important event causing quality loss of foods, especially those containing highly unsaturated fats. There is growing interest in replacing synthetic antioxidants in food by natural counterparts. Olive leaf is an abundant by-product of the olive oil industry. The aim of this study was to investigate the antioxidant capacity of olive leaf powder (OLP) in minced Atlantic horse mackerel stored at 4 8C over 3 days. OLP was introduced in the minced at concentrations of 0 (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…In general, the sausages presented considerable amounts of FA and during storage, it was possible to identify polyunsaturated fatty acids (PUFAs) belonging to the omega‐3 family, such as α‐linolenic acid (up to 30 days) and eicosapentaenoic acid (EPA) (at the end of 60 days), even in small amounts. Products containing high composition in PUFAs are more susceptible to the rancidification (lipid oxidation) process (Albertos et al, ), causing loss of nutritional value and generating volatile compounds. The ratio ΣPUFAs/ΣSFA showed a decrease along the storage time, the values found were: 0.75 (0 day); 0.66 (15 days); 0.57 (30 days); 0.51 (45 days); and 0.49 (60 days).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the sausages presented considerable amounts of FA and during storage, it was possible to identify polyunsaturated fatty acids (PUFAs) belonging to the omega‐3 family, such as α‐linolenic acid (up to 30 days) and eicosapentaenoic acid (EPA) (at the end of 60 days), even in small amounts. Products containing high composition in PUFAs are more susceptible to the rancidification (lipid oxidation) process (Albertos et al, ), causing loss of nutritional value and generating volatile compounds. The ratio ΣPUFAs/ΣSFA showed a decrease along the storage time, the values found were: 0.75 (0 day); 0.66 (15 days); 0.57 (30 days); 0.51 (45 days); and 0.49 (60 days).…”
Section: Resultsmentioning
confidence: 99%
“…This fact occurred due to the higher fats content present in MF (23.32%) compared to tilapia fillet (2.42%), used as raw materials (Table ). According to Albertos et al () and Brodowska et al (), products containing high composition in polyunsaturated fatty acids are more susceptible to the rancidification (lipid oxidation) process. Moreover, according to Luna, Lábaque, Zygadlo, and Marin (), lipid oxidation is the main cause for MF deterioration, as well as for meat products that contain it in its formulation.…”
Section: Resultsmentioning
confidence: 99%
“…According to Albertos et al (2018) and Brodowska et al (2016), products containing high composition in polyunsaturated fatty acids are more susceptible to the rancidification (lipid oxidation) process.…”
Section: Chemical and Physicochemical Characterizationmentioning
confidence: 99%
“…Sesamol and olive leaf extracts were effective as natural functional ingredients in retarding lipid oxidation in fresh or heat-processed pork sausages kept at 4°C for 21 days (Hayes, Stepanyan, Allen, O'Grady, & Kerry, 2011), while Pateiro et al (2018) have shown that guarana seed extracts delayed lipid oxidation in pork patties during refrigerated storage. Also, Albertos et al (2017) showed that olive leaf powder is a valuable source of natural antioxidants and can be used to protect minced fish muscle from lipid oxidation.…”
Section: Lipid Oxidationmentioning
confidence: 99%